Value of Image Fusion in Coronary Angiography for the Detection of Coronary Artery Bypass Grafts. Issue 6 (June 2016) - Plessis, Julien; Warin Fresse, Karine; Cahouch, Zachary; Manigold, Thibaut; Letocart, Vincent; Le Gloan, Laurianne; Guyomarch, Béatrice; Guerin, Patrice
Abstract : Background: Coronary angiography is more complex in patients with coronary artery bypass grafts (CABG). Image fusion is a new technology that allows the overlay of a computed tomography (CT) three‐dimension (3D) model with fluoroscopic images in real time. Methods and Results: This single‐center prospective study included 66 previous CABG patients undergoing coronary and bypass graft angiography. Image fusion coronary angiographies (fusion group, 20 patients) were compared to conventional coronary angiographies (control group, 46 patients). The fusion group included patients for whom a previous chest CT scan with contrast was available. For patients in this group, aorta and CABG were reconstructed in 3D from CT acquisitions and merged in real time with fluoroscopic images. The following parameters were compared: time needed to localize the CABG; procedure duration; air kerma (AK); dose area product (DAP); and volume of contrast media injected. Results are expressed as median. There were no significant differences between the 2 groups in patient demographics and procedure characteristics (access site, number of bypass to be found, and interventional cardiologist's experience). The time to localize CABG was significantly shorter in the fusion group (7.3 versus 12.4 minutes; P =0.002), as well as the procedure duration (20.6 versus 25.6 minutes; P= 0.002), AK (610 versus 814 mGy; P= 0.02), DAP (4390 versus 5922.5 cGy·cm 2 ; P =0.02), and volume of iodinated contrast media (85 versus 116 cc; P =0.002). Conclusions: 3D image fusion improves the CABG detection in coronary angiography and reduces the time necessary to localize CABG, total procedure time duration, radiation exposure, and volume of contrast media.